Studentská geologická konference 2020 Sborník abstraktů - Cígler, Vojtěch; Sobek, Kamil; Pořádek, Přemysl; Daňková, Ludmila (Masaryk University Press, 2020)
Title in English: Student geological conference 2020: Conference proceedings Student geological conference proceedings. Conference was held at Faculty of Science, Masaryk University in Brno on October 23th 2020. Department of Geological Sciences was organizer in cooperation with the Czech Geological Society.